Situation Report: Hungary, 23 February 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Dogmatists Still Oppose Private Sector The Problems of Disseminating Cultural Products Abroad Building Industry Exports - A New Source of Hard Currency New Tasks of the Hungarian Chamber of Commerce Past Performance and Future Role of Catholic Weekly Vigilia Introduction of Five-Day Week Earlier than Scheduled